Bycatch of a Critically Endangered Shark Glyphis glyphis in a Crab Pot Fishery: Implications for Management - Pillans, Richard D.; Fry, Gary C.; Carlin, Geoff D.; Patterson, Toby A. (Frontiers in Marine Science, 2022)
The speartooth shark Glyphis glyphis is a Critically Endangered shark only recorded in a few tropical river systems and coastal areas in northern Australia and Papua New Guinea. There is limited genetic exchange in populations residing in northern Australian rivers that are greater than 100 km apart. In Queensland, the species is only found in the Wenlock and Ducie River that flow into Port Musgrave. Acoutic monitoring from 2013 – 2021 showed juveniles are confined to upstream reaches of these rivers with seasonal downstream movement related to freshwater influx. This region also supports commercial and recreational fisheries including crab pot and gillnet fisheries. Following anecdotal reports of juvenile speartooth sharks being captured in crab pots, we investigated catch rates in crab pots experimentally in 2019 and 2020. Being obligate ram-ventilators, entrapment in crab pots results in mortality of bycaught speartooth sharks after a few hours Commercial fishing effort in the Wenlock and Ducie River was obtained from logbook data between 1993 - 2020. Twenty four juvenile (55 – 80 cm Total Length ) speartooth sharks were captured in experimental crab pots in the Ducie River and Tentpole Creek (a tributary of the Wenlock River) with catch rates high; up to 0.82 (± 1.86 SD) sharks.pot-1.s24h-1.. Experimental catch rates in crab pots varied between rivers and with distance upstream and were highest in areas of highest shark density based on detection of acoustically tagged sharks over seven years.. Although commercial crab effort varies spatially and temporally in relation to current catch rates and market demands, consistent monthly overlap with juvenile speartooth shark core distribution occurred throughout the year. Using experimental CPUE data multiplied by fishing effort in Tentpole Creek, we estimate that in November alone, between 51 to 279 speartooth sharks are potentially captured in years with high fishing effort. Bycatch of juvenile speartooth sharks in commercial and recreational crab pots poses a significant threat to this genetically isolated and small population. Urgent management intervention either through spatial management or modification to pot design that prevent sharks entering and/or enable them to escape are required ensure the viability of this population.